THE EFFECT OF STORYTELLING AND SOCIAL SKILLS METHODS ON SPEAKING SKILLS AGE 5-6 YEARS AT PAUD RA AL-MAHIR PERCUT SEI TUAN - Raodah Raodah; Sri Milfayetty; Aman Simare-mare (Sensei International Journal of Education and Linguistic, 2021)
Research it aims to: (1) MKnowing the difference in the speaking ability of children taught by the storytelling method compared to children taught using the conversation method; (2) Knowing the difference in speaking ability of children with high social skills and children with low social skills; and (3) Knowing the interaction of learning methods and social skills in influencing early childhood speech skills.The sample in this study is children in grades B1 and B2 as many as 32 students. Collecting data in this study used the observation guidelines for social skills and observation guidelines for early childhood speaking skills. Hypothesis testing is done by using the Two Way Anova test. The results showed that: (1)There is a significant difference between the children's speaking skills taught by the storytelling method compared to the conversational method (Fcount = 26.925 and sig. 0.000> 0.05); (2) The speaking skills of children who have high social skills are higher than those who have low social skills (Fcount = 11.867 and sig. 0.043> 0.02); and (3) There is an interaction between learning methods and social skills in influencing children's speaking skills (Fcount = 13.618 and sig. 0.001> 0.05)